The Effect of Oxytocin Massage on the Fundal Height of Multiparous Mother on the First until Tenth Day of Postpartum - Mayasari Putri Ardela; Nara Lintan Mega Puspita; Lindha Sri Kusumawati; Sunaningsih Sunaningsih (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: The Maternal Mortality Ratio (MMR) is still far from the target of Sustainable Development Goals (SDGs) which is 70 per 100,000 live births in 2030. Nationally, the main cause of maternal death is due to bleeding. One effort to prevent the occurrence of postpartum hemorrhage is oxytocin massage. This massage can stimulate the oxytocin hormone so that the uterine involution process can run normally. Purpose: This research aims to determine the effectiveness of the massage of oxytocin on the acceleration of uterine involution on the multiparous mother since the first day until the tenth day of postpartum. Methods: The design of this research is the quasi-experiment with a post-test with the control group on 20 persons that are determined by purposive sampling. The research samples were divided into 2 groups, i.e. 10 people were given a massage of oxytocin and 10 people were not massaged. Results: The results showed a significant reduction in fundal height (One-Way Anova p <0.05) with an average declining more than 1 cm. Conclusion: From the results of this study, it can be concluded that the massage of oxytocin can accelerate the high decline of uterus fundus.